2014
DOI: 10.1007/s11605-014-2489-1
|View full text |Cite
|
Sign up to set email alerts
|

Early Oral Feeding vs. Traditional Feeding in Patients Undergoing Elective Open Bowel Surgery—a Randomized Controlled Trial

Abstract: In patients undergoing elective open bowel surgeries, early post-operative feeding is safe, is well tolerated and reduces the length of hospitalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
45
1
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 29 publications
6
45
1
3
Order By: Relevance
“…We found that the mean number of days on minimal nutrition, either nil by mouth or on clear fluids, was threefold higher in patients with PPOI compared to those without PPOI (6.6 vs 2.6 days, respectively) (Table ), and this was positively associated with their LOSH (r = 0.66, P < 0.01) (Figure ). Our results support the findings of randomised control trials in which GI surgery patients who were fed on the first postoperative day had reduced incidence of PPOI and a shorter LOSH compared to patients for whom nutrition was delayed . Other studies have utilised early EN and found improved outcomes for patients after GI surgery, which were reportedly due to enhanced gut stimulation resulting from the EN .…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…We found that the mean number of days on minimal nutrition, either nil by mouth or on clear fluids, was threefold higher in patients with PPOI compared to those without PPOI (6.6 vs 2.6 days, respectively) (Table ), and this was positively associated with their LOSH (r = 0.66, P < 0.01) (Figure ). Our results support the findings of randomised control trials in which GI surgery patients who were fed on the first postoperative day had reduced incidence of PPOI and a shorter LOSH compared to patients for whom nutrition was delayed . Other studies have utilised early EN and found improved outcomes for patients after GI surgery, which were reportedly due to enhanced gut stimulation resulting from the EN .…”
Section: Discussionsupporting
confidence: 85%
“…Whether the patients’ nutrition was withheld as a result of their PPOI symptoms or was a causing factor cannot be determined from the data; however, when observing meal progressions for patients with PPOI, it was found that only 2 of the 18 patients received nourishing fluids before the diagnosis of PPOI and the others remained on minimal nutrition beyond the fourth day post‐surgery. Mean LOSH for all patients was 9.6 days, which is 3–4 days longer than that reported in previous trials for patients receiving ERAS care . Furthermore, when considering the burden of PPOI, it is notable that the readmission rate for PPOI patients in the present study was high compared to patients without PPOI (28 vs 8%, Table ).…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Those with few teeth often have poor oral hygiene, and tend to have poor oral status on admission . Additionally, reduced chewing and swallowing capacities caused by tooth loss compromise resumption of oral feeding after surgery and thus interfere with physical recovery . Therefore, those with few teeth might experience longer hospitalization for digestive cancer treatment, and extended hospitalization could increase medical costs.…”
Section: Discussionmentioning
confidence: 99%
“…Randomized studies of other gastrointestinal surgical patients have demonstrated that immediate postoperative oral feeding is associated with decreased incidence of complications, including ileus and anastomotic leak (3,4). Given the increased morbidity and mortality of esophagectomy relative to other gastrointestinal resections, there has been hesitance amongst thoracic surgeons to adopt this practice.…”
mentioning
confidence: 99%